Management of Patients Post Laminectomy Decompression Et Causa Spinal Cord Injury Cervical Vertebrae 1-7 with Hyperglikemia in Intensive Care Unit - Maulitia Neny Yusuprihastuti; Bowo Adiyanto; Johan Arifin (JAI (Jurnal Anestesiologi Indonesia))
Background: In the United States, in 2008 of 100,000 cases of spinal cord injury, 2/3 were cases of cervical injury. Patients who experience cervical to thoracic Spinal Cord Injury (SCI) above T8, usually have impaired function of the diaphragm and intercostal muscles which causes respiratory failure. Neurogenic shock occurs in patients who experience SCI above T6 which causes vasodilation, hypotension and severe bradycardia or asystole when stimulating vagal reflexes such as laryngoscopy or suctioning.